The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000507829
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Positive End-Expiratory Pressure Using Self-Inflating Bags during Newborn Resuscitation Is Possible Despite Mask Leak

Abstract: Background: Ventilation is the key intervention to resuscitate non-breathing newborns. Positive end-expiratory pressure (PEEP) may facilitate lung-liquid clearance and help establish functional residual capacity. Objectives: The aim of this study was to describe how mask leak and ventilation rates affect delivered PEEP and tidal volumes during newborn resuscitations using a self-inflating bag with an integrated PEEP valve. Methods: This was an observational study including near-term/term newborns who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…Our results are in agreement with Gomo et al ( 21 ) who found that mask leakage itself did not impair tidal volume delivery. We found a median mask leak of 30% with feedback and 70% without feedback, but a VT e within the recommended range.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in agreement with Gomo et al ( 21 ) who found that mask leakage itself did not impair tidal volume delivery. We found a median mask leak of 30% with feedback and 70% without feedback, but a VT e within the recommended range.…”
Section: Discussionsupporting
confidence: 94%
“…We found a median mask leak of 30% with feedback and 70% without feedback, but a VT e within the recommended range. Gomo et al ( 21 ) speculated that the leak is not constant but dynamic, which suggests that some variation in leakage and VT e can be tolerated. Notably, in our study, the fraction of correct VT e ’s was very low both in the skills training and simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Paper III in relation to other ventilation parameters using data from the PEEP-study. 237 PEEP well within intended values was found with mask leak up to 80%, and delivered PEEP was minimally affected by ventilation frequency. The results were significantly different from the results found in the manikin studies mentioned above.…”
Section: Gomo Et Al Has Further Explored the Reliability Of The Peep-...mentioning
confidence: 61%
“…Papers published by the group range from epidemiological studies and studies to evaluate cost effectiveness of interventions 192,[225][226][227][228][229] via studies of machine learning for automatic interpretation of data [230][231][232] to studies to describe practise, 196 evaluate effect of training methodologies, [233][234][235][236] studies to improve understanding of the basic physiology of newborn transition and resuscitation 74,134,138,221,237 and RCTs to compare new equipment to existing standards. 238,239…”
Section: Helping Babies Breathementioning
confidence: 99%
“…Die Produkteigenschaften verschiedener T-Stück-Systeme und auch selbstfüllender Beatmungsbeutel variieren erheblich, mit Auswirkungen während ihrer Verwendung [243]. Ein neueres vertikales Design von sich selbstfüllenden Beatmungsbeuteln und eine überarbeitete Maske bieten möglicherweise Vorteile in der Handhabung und bei der Verwendung eines endexspiratorischen Drucks [190,[244][245][246].…”
Section: Hilfsmittel Zur Assistierten Beatmungunclassified